CHarity and donation tracking system using queue structure - Badheyba, Manea Abdullah; Rozlina, Mohamed (Institute of Electrical and Electronics Engineers Inc., 2023)
With the advent of new technology and online payment systems, acquiring donors for charitable causes has become easier. However, the donation process often ends for donors once they have made their contribution, leaving the remaining work to the charity. This lack of visibility and involvement can lead to donor disengagement and hinder future contributions. To address this problem, we propose implementing a comprehensive donor tracking system that uses the queue which operates on a first-in, first-out (FIFO) basis. This system ensures that the first donor's donation is prioritized and fulfilled before the second donor can utilize and benefit from their donation. This system aims to provide real-time updates on the progress and impact of donations, bridging the gap between donors and beneficiaries. Existing online donation platforms often focus solely on facilitating payments, neglecting post-donation tracking. This lack of transparency leaves donors unaware of how their contributions are utilized and whether they reach the intended beneficiaries, potentially affecting donor trust and confidence. By implementing the queue method, charities can streamline donation workflows, track, and acknowledge donations, and provide transparency to donors. When we examine the current tracking methods used in the donation field, it becomes evident that only a limited number of methods, and only blockchain-based systems are in use. Unfortunately, these systems tend to escalate costs significantly. This paper highlights the how and what are the benefits of adopting the queue method for donor tracking, including improved donor engagement and trust. Ultimately, the proposed system enhances donor satisfaction and maximizes the impact of charitable giving.